1999
DOI: 10.1002/(sici)1521-4141(199910)29:10<3262::aid-immu3262>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic regulation of CD8+ T cells by perforin

Abstract: To prevent uncontrolled expansion, the massive proliferation of T cells during an acute immune response has to be followed by controlled deletion. Here we show that similar to Fas, perforin is not only an important effector molecule of cytotoxic T lymphocytes (CTL) but also involved in down‐regulating peripheral T cells. Mice deficient for both the CTL effector molecule perforin and the apoptosis‐inducing Fas ligand spontaneously develop infiltration of highly activated CD8+ T cells in kidney and liver and die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
2
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 54 publications
7
87
2
3
Order By: Relevance
“…These results suggest that IL-1␤ and NO do not play major pathogenic role in this model of T1D. In contrast, NOD mice deficient in TNF receptor 1 do not develop spontaneous diabetes, and TNF receptor 1-deficient ␤ cells are resistant to killing by CD4 ϩ T cells (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that IL-1␤ and NO do not play major pathogenic role in this model of T1D. In contrast, NOD mice deficient in TNF receptor 1 do not develop spontaneous diabetes, and TNF receptor 1-deficient ␤ cells are resistant to killing by CD4 ϩ T cells (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that abnormal cytotoxic cells may fail to provide appropriate apoptotic signals for removal of activated macrophages and T cells during the contraction stage of some immune responses leading to persistent expansion of T cells and macrophages secreting proinflammatory cytokines. 34,35,37 As a result of continuous stimulation with proinflammatory cytokines (most notably, interferon gamma (IFNg)), macrophages will become hemophagocytic. 33,38 Although familial cases of MAS in sJIA have not been reported, as in FHLH, sJIA/MAS patients may also have functional defects in the exosome degranulation pathway.…”
Section: Genetic Factors For Mas In Sjiamentioning
confidence: 99%
“…Despite a similar degree of graft-vs.-host disease and normal Fas-mediated apoptosis, pko T cells are able to expand to greater numbers in allogeneic SCID mice than cells taken from wild-type donors [16]. In addition, while wild-type mice show deletion of specific activated CD8 + cells after persistent LCMV infection or after injection with staphylococcal enterotoxin B, pko mice accumulate reactive T cells and die of immune-mediated damage [17,18]. Furthermore, perforin defects in young human patients with familial hemophagocytic lymphohistiocytosis result in splenomegaly, accumulation of activated macrophages and lymphocytes, defective CTL and NK cytotoxicity, and elevated levels of serum IFN-+ and TNF- § [19], symptoms suggestive of a chronic inflammatory response and failure of AICD among other things in the absence of perforin.…”
Section: Introductionmentioning
confidence: 99%